Resepsi Fungsional Terhadap Manuskrip Mushaf Al-Qur’an di Dusun Pallarangan Desa Simbang Kecamatan Pamboang Kabupaten Majene - Ta'bori, Makmur; Nur Hikma Yanti; Syarif Abbas (Al-Aqwam: Jurnal Studi Al-Quran dan Tafsir, 2024)
This article presents a functional reception of manuscripts of the Qur’an in Pallarangan Hamlet, Simbang Village, Pamboang District, Majene City. The object of research is the Pallarangan community which consists of religious leaders, community leaders and ordinary people. The aim of the research is to describe and analyze the functional reception of the Pallarangan community towards manuscripts of the al-Qur’an in Pallarangan hamlet. This paper is based on qualitative descriptive research. The method applied is the living Qur’an which is based on the results of interviews and observations. The sources were taken randomly from religious leaders, community leaders and the general public in Pallarangan Hamlet, Simbang Village, Majene City. Based on data analysis, it was found that the Qur’an manuscript was used as a medium for treating sick residents. The procedure used to treat residents with a manuscript of the Qur’an is to place the manuscript of the Qur’an on water and then hold it while rotating it around the water to be drunk by the patient while reciting special prayers. Apart from being used to treat sick residents, the manuscript was also used to ward off evil, and was used to inaugurate village heads as an oath.